2018
DOI: 10.1038/s41598-018-31432-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and molecular basis for carbohydrate increase and nitrate reduction in burley tobacco seedlings by glycerol through upregulating carbon and nitrogen metabolism

Abstract: Burley tobacco (Nicotiana Tabacum) is a chlorophyll-deficiency mutant. Nitrate is one precursor of tobacco-specific nitrosamines (TSNAs) and is largely accumulated in burley tobacco. To decrease nitrate accumulation in burley tobacco, glycerol, a polyhydric alcohol compound and physiological regulating material, was sprayed and its effects were investigated based on metabolomic technology and molecular biology. The results showed that glucose, glutamine and glutamic acid increased by 2.6, 5.1 and 196, folds, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Photoperiod or light duration is another vital environmental factor regulating plant flowering, morphogenesis, and metabolism. The extension of light duration or modification of the photoperiod using artificial light sources can increase carbohydrate synthesis, which stimulates nitrate assimilation by providing a continuous supply of reductant energy and carbon skeletons [ 48 ]. After being taken up from the soil and transported into different organs, nitrates are generally stored in the vacuole in the dark [ 49 ].…”
Section: Nitrate Assimilation and Accumulation In Vegetables In Rementioning
confidence: 99%
“…Photoperiod or light duration is another vital environmental factor regulating plant flowering, morphogenesis, and metabolism. The extension of light duration or modification of the photoperiod using artificial light sources can increase carbohydrate synthesis, which stimulates nitrate assimilation by providing a continuous supply of reductant energy and carbon skeletons [ 48 ]. After being taken up from the soil and transported into different organs, nitrates are generally stored in the vacuole in the dark [ 49 ].…”
Section: Nitrate Assimilation and Accumulation In Vegetables In Rementioning
confidence: 99%
“… 2017 ; Li et al. 2018 ). Moreover, metabolomics is accepted to comprehensively evaluate endogenous metabolites of a biological system holistically, and its property is consistent with the holistic efficacy of Chinese medicine (Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, a growing number of studies prove that gut microbiota interferes with gastrointestinal physiology, metabolism, and immune function of the host, and influences central nervous system (CNS) function and behaviour via the microbiota-gut-brain (MGB) axis (Foster and McVey Neufeld 2013 ; Luna and Foster 2015 ; Li et al. 2018 ). The delicate imbalance of gut microbiota is implicated in numerous human diseases, such as sleep loss, circadian misalignment, affective disorders, and metabolic disease (Agus et al.…”
Section: Introductionmentioning
confidence: 99%
“…In ginseng, however, the two advantageous phenotypes may not only provide resource of energy during seed gemination but also increase the capacity to capture limited light under shaded habitat. For physiological traits, both the one-year and four-year ginseng plants possessed relatively lower light saturation point (300-400 μmol·m -2 ·s -1 ) compared to Arabidopsis (700-800 μmol·m -2 ·s -1 ) and other heliophytic plant species (600-1000 μmol·m -2 ·s -1 ) (Boonchai et al ., 2018; Li et al ., 2018). In particular, we showed that both one-year and four-year ginseng plants exhibited significantly higher Fv/Fm values under dim-light compared to sunlight condition.…”
Section: Discussionmentioning
confidence: 99%